Robust HPV‐16 Detection Workflow for Formalin‐Fixed Cancer Tissue and Its Application for Oral Squamous Cell Carcinoma - Shizuka Morodomi; Akiyuki Hirosue; Akhinur Rahman; Kyotaro Nohata; Misaki Matsuo; Omnia Reda; Samiul Alam Rajib; Haruki Saito; Hiroki Takeda; Ryoji Yoshida; Masafumi Nakamoto; Masatoshi Hirayama; et al. (Cancer Medicine)
ABSTRACT Background Virus‐related cancers are malignancies caused by specific viruses, such as human papillomavirus (HPV), hepatitis B virus, and human T‐cell leukemia virus, contributing significantly to the global cancer burden through persistent infection and oncogenic transformation. The current study aimed to develop a robust HPV‐16 detection method for formalin‐fixed cancer specimens. Materials and Methods To prevent false negatives resulting from DNA fragmentation, a DNA quality check step was added. Additionally, this study used multiplex polymerase chain reaction (PCR) covering the entire HPV‐16 genome to mitigate effects caused by viral sequence variation. To prove this concept, we analyzed genomic DNA extracted from oropharyngeal cancer tissues known as HPV‐16‐positive. Subsequently, the protocol was tested on oral squamous cell carcinoma (OSCC) samples in our cohort. Given the wide variation in HPV‐16 positivity in previous studies, it remains elusive how frequently HPV‐16 is positive in OSCC. Results The results showed faint bands or smears in the multiplex PCR of 7 out of 112 cases. Droplet digital PCR confirmed variable positivity levels of HPV‐16, suggesting two scenarios of HPV‐16 positivity in cancer tissue: cancer cells derived from infected cells or only a portion being HPV‐16‐positive. Finally, we comprehensively analyzed the case and identified the integration of a deleted HPV‐16 genome into the intronic region of the host gene TMEM94 on chromosome 17. To the best of our knowledge, this is the first evidence showing the integration of HPV‐16 in OSCC cells and providing its complete viral sequence. Conclusions The established protocol should be applicable to various cancer tissues for analyzing the association with HPV‐16 infection.